Impacto da difusão de tecnologia na melhoria da qualidade do leite - Coloni, Rodrigo Dias [UNESP] (2015)
The objective of the study was to evaluate the diffusion of technology for dairy farming family farmers aimed at improving the quality of milk through diagnostics, training and monitoring of trained extension workers disclose to farmers. The study was conducted with 550 properties to identify the profile of the total producers in relation to family farmers in the Ribeirão Preto region, along with dairy cooperative and CATI program MILK / SAA / SP. Of this total was conducted sampling of 143 producers in 50 received technical assistance trained with a focus on milk quality through theoretical and practical courses according to your needs and only 93 were monitored through the milk analysis. All 50 producers were monitored and evaluated monthly for 12 months through technical visits of trained technical assistants. Visits were carried techniques for data collection and milk samples for monitoring the quality of milk and the use of the techniques covered in the courses. It was found significant improvement of milk quality due to the support of technical assistance and that the quality of milk produced by family farmers did not differ in the quality of the milk producers employers